Theoretical Analysis on the Measurement Errors of Local 2D DIC: Part I Temporal and Spatial Uncertainty Quantification of Displacement Measurements. (23rd December 2015) - Wang, Y.; Lava, P.; Reu, P.; Debruyne, D.
Abstract: This paper presents a theoretical uncertainty quantification of displacement measurements by subset‐based 2D‐digital image correlation. A generalised solution to estimate the random error of displacement measurement is presented. The obtained solution suggests that the random error of displacement measurements is determined by the image noise, the summation of the intensity gradient in a subset, the subpixel part of displacement, and the interpolation scheme. The proposed method is validated with virtual digital image correlation tests.